Mirror-terminated Mach-Zehnder interferometer based on SiNOI slot and strip waveguides for sensing applications using visible light - Sultan, Alaa; Sabry, Yasser M.; Samir, Ahmed; El-Aasser, Mostafa A. (Frontiers in Nanotechnology, 2023)
In this work, a highly sensitive sensor made of silicon nitride (SiN) waveguide is proposed that can be used for gas sensing using visible light. The whole sensor waveguide uses a silicon dioxide (SiO2) cladding while the sensing arm uses a fluidic cladding such as water. The proposed device is based on loop-mirror terminated (LMT) Mach-Zehnder interferometer (MZI), where the reference arm is exposed to the reference SiO2 medium, while the sensing arm is exposed to the sensing medium leading to a change in the refractive index of the waveguide cladding. The sensor performance is overall optimized by optimizing the design performance of all the components of the structure one by one. The waveguide sensitivity of both strip and slot types is analyzed for gaseous medium in order to compare their sensitivities and select the dimensions of the waveguide that results in the highest device sensitivity. Transverse-electric (TE) polarization is considered in this study for strip waveguide, where a higher sensitivity is founded with respect to the transverse-magnetic (TM) polarization. The field confinement in the slot waveguide in the sensing region is investigated and verified with a mode solver, where the optimum dimensions are obtained using finite difference eigenmode and finite difference time domain solvers. With a sensing arm length of 150 μm only, the proposed sensor achieves a device sensitivity of about 1320 nm/RIU and a figure-of-merit (FOM) as high as 641 RIU−1 at the wavelength of 650 nm, which is the highest reported FOM up to the author’s knowledge. Higher values of the FOM are possible by employing a longer sensing arm.